The application of sustainable organic farming with hydroponic system for farmers in Gending Village - Ihyak Mustofa; Mas Ahmad Baihaqi; Zico Awalatul Badar (University of Merdeka Malang, 2022)
Gending Village is a village located in Gending District, Probolinggo Regency which is used as one of the economic centers in Probolinggo Regency. This causes 60 percent of the land for cultivation to be converted to industrial areas. As written in detik.com Daily on Wednesday, Jan 16, 2019. Hydroponics is a system for cultivating plants without using soil media but using water media that contains minerals and nutrients. The purpose of the socialization activity on the application of organic farming with hydroponic methods for farmers in Gending Village is to increase the knowledge of farmers in Gending Village regarding alternative solutions to the problem of increasingly narrow agricultural land. The implementation method in this activity is by direct socialization. The socialization about hydroponics was carried out with the help of PowerPoint slides and videos of hydroponic making practices that had been previously made by the KKN Parading team. After that, it was followed by a discussion and question and answer session with the farmers in Gending village regarding the material that had been delivered. The result of this activity is hydroponic equipment and plants which are distributed to farmers who take part in socialization activities and distributed to residents